Selskabsstyring i unoterede virksomheder: Hvad ved vi, og hvad kan det bruges til? - Morten Bennedsen (Copenhagen Business School (CBS), Department of Economics, 2006)
– I provide a short survey on recent research on the governance of closely held corporations. I focus on the strategic choice of ownership structure, the creation of family firms and the role of the board in the closely held corporation. Attention is payed to policyimplications of the research results.
hdl:10398/7524
Keywords: H00; 330; governance; corporations; ownership structure; family firms